Can SMEs survive climate change? Eva Marie Arts and Crafts versus Typhoon Yolanda - Castillejos, Maryjo Therese Y (Archīum Ateneo, 2014)
On 8 November 2013, Typhoon Yolanda — the strongest storm ever to make landfall in recorded history — hit the Philippines. As part of its repercussions, a storm surge of anywhere from 3 to 5 meters (10-17 feet) in height hit the islands of Leyte and Samar. Typhoon Yolanda devastated many micro, small and medium sized enterprises (SMEs), not merely in terms of their infrastructure, but also by harming workers, disrupting supply chains, and crippling public services. Many are concerned that the recovery from the aftermath of typhoon Yolanda will be much slower if the enterprises forming the backbone of the domestic economy are unable to resuscitate investments and job creation in the area. And if storms like Yolanda increase in frequency and intensity due to climate change, then there is also the concern that only larger firms will be able to adapt with strong disaster risk management strategies. On the other hand, SMEs could systematically lose out, reducing their competitiveness and marginalizing them in disaster-prone economies. To help identify and illustrate the important factors that might influence the abovementioned outcomes, this case focuses on the production chain of Eva Marie Arts and Crafts, Inc., a handicraft producer in Basey, Samar. The case describes how this particular enterprise (a small-scaled firm) fared when Typhoon Yolanda struck. It illustrates the important linkages across the resilience of this firm with the resilience of the entire production chain to which it belongs.